Financial development, growth and volatility: A brief review of recent literature - Cermeño, Rodolfo; Roa, María José (Estudios Económicos de El Colegio de México, 2014)
This note presents a brief summary of the recent literature, both theoretical and empirical, on the effects of financial development on growth and growth volatility. We attempt to contribute to the analysis of the possible channels of interaction between these processes which is key for policies aimed to promote growth and reduce growth volatility.